Spinal Cord Tethering after Trauma and Impact of Age and Surgical Outcome - Haider Ali Khattak, Badar Uddin Ujjan, Tauseef Raza, Nasim Gul, Aurangzeb Kalhoro, Usamah Bin Waheed, Faizan G Mustafa, Muhammad Adeel (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Spinal cord tethering, a condition where the spinal cord becomes attached or fixed to surrounding tissues, can occur following trauma, leading to a range of neurological deficits and complications. Objectives: The main objective of the study is to find the spinal cord tethering after trauma and impact of age and surgical outcome in local population of Pakistan. Material and methods: This retrospective study was conducted in Ayub Medical Complex Abbottabad from January 2023 to August 2023. Data was collected from 50 patients of spinal cord tethering patients. Data collection involved a comprehensive review of the medical records of patients. Relevant demographic information, including age at the time of trauma, gender, and comorbidities, was extracted. Clinical details such as mechanism of injury, level and severity of spinal cord injury, duration of symptoms and preoperative neurological status were documented. Results: Data were collected from 50 SCI patients. The mean age of the patients was 45 ± 10.5 years and there were 60% male and 40% female patients. The most common mechanisms of injury were motor vehicle accidents (50%), followed by falls (30%) and sports-related injuries (20%). Regarding the spinal level affected, the majority of injuries were cervical (60%), followed by thoracic (30%) and lumbar (10%). Neurological improvement was observed in 40% of patients, with complete improvement in 40% and partial improvement in 20%, while 40% showed no improvement. Complications were reported in a subset of patients, with cerebrospinal fluid leaks occurring in 15%, wound infections in 10%, and other complications in 5% of cases. Reoperation was necessary in 10% of patients, while 90% did not require further surgical intervention. Age and neurological improvement showed non-significant differences between groups (p > 0.05), while length of hospital stay differed significantly (p = 0.018). Complications and functional improvement did not vary significantly between groups (p > 0.05) Practical Implication: This study’s practical implications offer vital benefits to the community. The identification of age as a critical component in spinal cord tethering after trauma enables healthcare practitioners to more accurately evaluate risk and customize therapies. Furthermore, our research emphasizes how successful surgical therapies are for patients of all ages, giving patients confidence in their available treatment alternatives. Further improving patient care is pushing for individualized treatment options and being aware of related consequences.